The Existence of Fraud Indicators in Insurance Industry: Case of Jordan - Al Rawashdeh, Firas Mohammad; Al Singlawi, Omar (International Journal of Economics and Financial Issues, 2017)
Insurance industry is playing a vital role in modern economies and it considered as one of the large industries in global context , it is facing many challenges and facing many types of risks , one of these risks is fraud risk ,since insurance industry in Jordan considered as one the most important economic sector this study came to investigate the possible existence of fraud indicators in this industry , a four variables have been chosen that are; effective internal systems and possible fraudulent practices committed by Insured parties Intermediates or /and brokers & complementary service providers. A questionnaire has been used and sent to a (25) insurance companies of a total (75) questionnaires,(56) were returned , valid and included in the analysis. Hypothesis testing relied mainly on descriptive statistics like median, mean and standard deviations. The results showed that it was statistically significant with significance level at 0.00. the existence of fraud indicators in insurance companies. The study has concluded that these indicators are existed in different aspects of insurance business and it recommended that insurance companies in Jordan have to improve insured party’s understanding and awareness regarding insurance services and should cooperate and capitalize on the efforts of supervision authorities toward fighting this issue, also supervision authorities should develop and promote best practice’ guidance that enhance the effectiveness of insurance companies. Keywords: Insurance Companies, Insurance Fraud, Broker, complementary services. JEL Classifications: D81, G220, G240, P43.